1984
DOI: 10.1068/p130647
|View full text |Cite
|
Sign up to set email alerts
|

Selective Looking and the Müller-Lyer Illusion: The Effect of Changes in the Focus of Attention on the Müller-Lyer Illusion

Abstract: According to a selective looking paradigm subjects were required to attend to the inward-going or outward-going components of a combined Müller-Lyer figure in which both components were present and distinguishable by colour. The amount of the illusion was found to vary according to which component the subject attended. Subsidiary findings relate the amount of the illusion to fin angle, fin length, and length of shaft.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
23
0

Year Published

1988
1988
2005
2005

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 9 publications
2
23
0
Order By: Relevance
“…The mechanism underlying the attentional effect found here, and related effects found elsewhere (Goyro et al, 1984;Predebon, 2004), is unknown although visual scanning patterns is one possibility. Plausibly, the instruction to attend to the shaft induced a change in scanning behaviur in the direction of observers either their restricting their eye movements along the shaft or restricting the focus of their visual attention (Posner, 1978) onto the shaft.…”
Section: Resultsmentioning
confidence: 73%
See 1 more Smart Citation
“…The mechanism underlying the attentional effect found here, and related effects found elsewhere (Goyro et al, 1984;Predebon, 2004), is unknown although visual scanning patterns is one possibility. Plausibly, the instruction to attend to the shaft induced a change in scanning behaviur in the direction of observers either their restricting their eye movements along the shaft or restricting the focus of their visual attention (Posner, 1978) onto the shaft.…”
Section: Resultsmentioning
confidence: 73%
“…As was noted previously, observers' attentional set or viewing attitude (i.e., 'part-isolating' versus 'whole' attitude) can significantly alter illusion magnitudes (Di Nuovo, 1984;Gardner & Long, 1961;Goyro, Robinson, & Wilson, 1984;Predebon, 2004). It has been suggested (e.g., Predebon et al, 1993;Predebon, 1998; see also Lewis, 1908) that attentional set may promote the occurrence of illusion decrement, independently of other decrement-inducing factors.…”
Section: Methodsmentioning
confidence: 85%
“…This suggests an optimal fin/shaft ratio of 36%. Goryo, Robinson, and Wilson (1984) evaluated shaft lengths that varied from 90 to 110 mm (4.5-5.5 deg) and with fin/shaft ratios of 10%,25%, and 40%. For concave and convex configurations alike, they found the greatest distortion with a fin/shaft ratio of 40%.…”
Section: Key Variables For Metric Distortionmentioning
confidence: 99%
“…Goryo et al (1984) examined (among other variables) shaft lengths subtending 4.5, 5.0, and 5.5 deg of visual angle. Across the three values, they found that illusion error was an increasing function of shaft length for concave configurations and a decreasing function of length for convex.…”
Section: Prior Studies Of Stimulus Spanmentioning
confidence: 99%
“…stimuli are viewed (see Coren & Girgus, 1978a, for a review). These strategies include confusion between the figural elements that contribute to the distortions (Coren & Girgus, 1972;Erlebacher & Sekuler, 1969), application of three-dimensional processing to two-dimensional arrays Gillam, 1971Gillam, , 1980Gregory, 1968;Ward, Porac, Coren, & Girgus, 1977;Warren & Bashford, 1977), averaging and/or contrast among figural elements (Coren & Miller, 1974;Girgus & Coren, 1982;Jordon & Uhlarik, 1986;Massaro & Anderson, 1971;Pressey, 1974;Restle & Decker, 1977), distribution of attention over the illusion figure (Coren & Porac, 1983;Goryo, Robinson, & Wilson, 1984), and implicit biases used to extract eye-movement information (Coren, 1986).…”
mentioning
confidence: 99%